Mining in Peru and Colombia: Challenges, Impacts and Opportunities for Sustainable Development - Pabón Trujillo , Herminio; Antonio Moya, Richard; Castro García, Ronald Iván; Trigos Bayona, Sergio Andrés; Isabel Peña, Teresa (Ciencia Latina Revista Científica Multidisciplinar, 2025)
Introduction: The purpose of this article is to know the different aspects of the mining sector of Peru vs. Colombia in everything that concerns labor protection and well-being. Mining makes up one of the most significant economic areas in Latin America, including Peru and Colombia, however, this high-risk activity requires rigorous standards in relation to health and care in the workplace, since this trade is characterized by being one of the most dangerous and with the greatest possibility of health risk for those who carry out this activity. The purpose of this analysis is to find out how safe the working conditions faced by these workers are, what regulations they are governed by or whether they are implementing measures to protect workers, in order to control the different dangers that this activity leaves behind. Objective: The main objective is to examine the current environment in terms of labor protection and physical and mental well-being, considering past experiences and current regulations of the results in the mining industry, comparing the progress and strategies implemented to guarantee safe working conditions. Methodology: This section is based on an exploration of documents from secondary sources, including official reports, laws, regulations, government reports, regulations, as well as academic studies on health and defense in the work environment in mining in Colombia and Peru, to achieve greater knowledge about this information in this sector. Results: It can be established that in the extractive mining sector in Peru and Colombia they face a chain of complications in terms of labor protection, this includes high rates of illnesses and incidents, although in Peru this has decreased; Also, in these two countries they have legal regulations to handle everything related to the protection of workers that help promote safe working conditions.